The role of fibroblasts in mycobacterial infections - Junjie LIN; Yang LI; Xiuqiu LIN; Min OU; Yunling YAN; Xiaohua WANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Mycobacterium is a gram-positive bacterium that causes chronic infectious diseases. Fibroblasts are widely present in various tissues and organs of the human body. They participate in the immune response to mycobacterial infections via multiple mechanisms such as interaction with macrophages, cellular immunity and secretion of active substances, and are associated with the formation and development of mycobacterial granuloma. In this paper, the role of fibroblasts in mycobacterial infections is reviewed to provide evidence for the prevention and treatment of mycobacterial infections.